2015
DOI: 10.1128/jvi.00974-15
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Nonnucleoside Reverse Transcriptase Inhibitor Resistance Mutations on Cytotoxic T Lymphocyte Recognition between HIV-1 Subtype B and Subtype A/E Infections

Abstract: The effect of antiretroviral drug resistance mutations on cytotoxic T lymphocyte (CTL) recognition has been analyzed in HIV-1 subtype B infections, but it remains unclear in infections by other HIV-1 subtypes that are epidemic in countries where antiretroviral drugs are not effectively used. We investigated the effect of nonnucleoside reverse transcriptase (RT) inhibitor (NNRTI)-resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…C1R cells expressing HLA-B*52:01 (C1R-B5201) and HLA-C*12:02 (C1R-C1202), and 721.221 cells expressing CD4 and HLA-C*12:02 (721.221-CD4-C1202) were previously generated [ 33 , 54 ]. These cells were cultured in RPMI-1640 medium (Invitrogen) containing with 5–10% fetal bovine serum (R5-R10) and 0.15 mg/ml hygromycin B. RMA-S-C1202 cells, a TAP deficient mouse-derived cell line that expresses HLA-C*12:02, were previously generated and cultured in R10 containing 0.15 mg/ml hygromycin B [ 55 ]. MAGIC-5 cells (CCR5-transfected HeLa-CD4/LTR-β-gal cells) were cultured in R10 as described previously [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…C1R cells expressing HLA-B*52:01 (C1R-B5201) and HLA-C*12:02 (C1R-C1202), and 721.221 cells expressing CD4 and HLA-C*12:02 (721.221-CD4-C1202) were previously generated [ 33 , 54 ]. These cells were cultured in RPMI-1640 medium (Invitrogen) containing with 5–10% fetal bovine serum (R5-R10) and 0.15 mg/ml hygromycin B. RMA-S-C1202 cells, a TAP deficient mouse-derived cell line that expresses HLA-C*12:02, were previously generated and cultured in R10 containing 0.15 mg/ml hygromycin B [ 55 ]. MAGIC-5 cells (CCR5-transfected HeLa-CD4/LTR-β-gal cells) were cultured in R10 as described previously [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…These cells express the same level of HLA-C14 on the cell surface. RMA-S-C1202 cells were generated in our lab as previously described (Kuse et al, 2015). RMA-S-C1402 and -C1403 cell lines were generated by the transfection of HLA-C*14:02 and -C*14:03 genes into RMA-S cell lines, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The current study definitively demonstrated that PolTY9 is an HLA-B*15:02-restricted epitope in subtype A/E infection. Out of 17 reported best-defined epitopes derived from the subtype A/E virus (Los Alamos HIV-1 database [ https://www.hiv.lanl.gov ]), 5 epitopes only were analyzed to examine their presentation by cells infected with HIV-1 subtype A/E in our previous studies ( 42 44 ). In this study, we demonstrated that T cells specific for HLA-B*15:02-restricted epitopes recognized cells infected with an HIV-1 subtype A/E clone established from an individual in our Hanoi cohort.…”
Section: Discussionmentioning
confidence: 99%